Forelimb musculoskeletal-tendinous growth in frogs - Soliz, Mónica Elizabeth (2020)
The tendons unite and transmit the strength of the muscles to the bones, allowing movement dexterity, the distribution of the strength of the limbs to the digits, and an improved muscle performance for a wide range of locomotor activities. Tissue differentiation and maturation of the structures involved in locomotion are completed during the juvenile stage; however, few studies have investigated the ontogenetic variation of the musculoskeletal-tendinous system. We ask whether all those integrated tissues and limb structures growth synchronically between them and along with body length. We examined the ontogenetic variation in selected muscles, tendons and bones of the forelimbs in seventy-seven specimens belonging to seven anuran species of different clades and of three age categories, and investigate the relative growth of the forelimb musculoskeletal-tendinous structures throughout ontogeny. Ten muscles and nine tendons and their respective large bones (humerus and radioulna) were removed intact, and their length was measured and analyzed through a multivariate approach of allometry. We obtained an allometry coefficient, which indicates how the coefficient departures from isometry as well as allometric trends. Our data suggest that along with the post-metamorphic ontogeny, muscles tend to elongate proportionally to bone length, with a positive allometric trend. On the contrary, tendons show a negative allometric growth trend. Only two species show different patterns: Rhinella granulosa and Physalaemus biligonigerus, with an isometric and positive growth of muscles and bones, and most tendons being isometric.